Determinants of Smallholder Vegetable Farmers Credit Access and Demand in Southwest region, Cameroon - Yannick F. Djoumessi; Cyrille B. Kamdem; Victor Afari-sefa; Jean-Claude Bidogeza (Economics Bulletin, 2018)
The study analyzed the determinants of smallholder vegetable farmer's access and demand to credit. Primary data were collected from hundred randomly selected farmers with the aid of structured questionnaires using multi-stage sampling procedures. One common approach used to modeling this situation is the Tobit model. However, the decision taken by farmers to demand credit is preceded by the decision to have “access to credit”. We find that the estimates from the Tobit model captured the demand decision at the level of access. Thus, the double-hurdle model seems appropriate to determine factors influencing credit demand. The study concluded that the spread of lending agencies, membership to farmers' association and agricultural extension services increase both access to and demand for credit. In addition, small-scale and female farmers should be encouraged to form associations to ensure appropriate information sharing and advantage of non-rationing credit.
Keywords: Q12; D01; C13; 330; credit access; credit demand; double-hurdle; small-scale vegetable farmers